Group Refractive Index of Nanocrystalline Yttria-Stabilized Zirconia Transparent Cranial Implants - Halaney, David L.; Katta, Nitesh; Fallah, Hamidreza; Aguilar, Guillermo; Milner, Thomas E. (Frontiers in Bioengineering and Biotechnology, 2021)
Transparent “Window to the Brain” cranial implants made from a biocompatible ceramic, nanocrystalline yttria-stabilized zirconia, were recently reported. These reports demonstrated chronic brain imaging across the implants in mice using optical coherence tomography (OCT) and laser speckle imaging. However, optical properties of these transparent cranial implants are neither completely characterized nor completely understood. In this study, we measure optical properties of the implant using a swept source OCT system with a spectral range of 136 nm centered at 1300 nm to characterize the group refractive index of the nc-YSZ window, over a narrow range of temperatures at which the implant may be used during imaging or therapy (20°C – 43°C). Group refractive index was found to be 2.1-2.2 for OCT imaging over this temperature range. Chromatic dispersion for this spectral range was observed to vary over the sample, sometimes flipping signs between normal and anomalous dispersion. These properties of nc-YSZ should be considered when designing optical systems and procedures that propagate light through the window, and when interpreting OCT brain images acquired across the window.